DAYA HAMBAT SAMPO ANTI KETOMBE TERHADAP PERTUMBUHAN C. albicans PENYEBAB KETOMBE - Ariyani . .; Sri Sinto Dewi; Ratih . Haribi (JURNAL KESEHATAN, 2009)
Abstract Anti-dandruff shampoos on the market are expected to inhibit the growth of Candida sp. on the Scalp, but the fact is not able to inhibit the growth of fungi that still occur as a manifestation of dandruff growth of Candida sp. The purpose of this study was to determine the growth of Candida sp. in media containing anti-dandruff shampoo. Types of research conducted experiments conducted in FIKKES UNIMUS Microbiology Laboratory. When the study in March and April 2006. Sample of pure cultures of Candida sp. Isolate BLK Semarang, and anti-dandruff shampoo containing active substances with Zn Pt O brand A, B, and C. Series of test done including manufacturing test solution consisting of shampoo solution with a concentration of 90%, 80%, 70%, 60%, 50%, suspicion Candida sp. contact time l, 2, 3, 4, and 5 minutes. Suspension Candida sp. Treated with test solution and planted in the medic and then incubated SGA 2x24 hours at a temperature of 370 C. Research results showed growth of Candida sp happen. on SGA medium (Glucose Saboroud order) which has been in contact with anti-dandruff shampoos A, B, and C at concentrations of 90%, with the Relative number of colonies decreased from the previous contact time of l, 2, 3, 4, and  5 minute. Of the three shampoos that can inhibit the growth of the fungus Candida sp. well is shampoo C. Conclusion that the higher konsetrasi shampoo and more time in contact with the higher shampoo inhibit the growth of shampoo for Candida sp. SGA to the media. Shampoo C labia have good inhibitory power than shampoo shampoo A and B. Keywords : anti- dandruff Shampoo, G r o w t h, Candida aIbicans